Technology's storytellers : - Staudenmaier, John M. (Society for the History of Technology and the MIT Press, 1985)
Contents: Technology's Storytellers documents the emergence of the history of technology as a coherent intellectual discipline. Based on an analysis of nearly 300 articles published in Technology and Culture, it proposes a mode of historical research as a communal rather than an individualistic endeavor -- looking for patterns of consensus in the authors' choice of time periods, geographical locations, and types of technology to study. It discusses the recurrent themes of the relationship between science and technology and the cultural ambience of technology, and examines the extent to which historians are moving away from a once pervasive ideology of autonomous technological progress.Co-published with the Society for the History of Technology.